Modern annual deposition and aerial pollen transport in the Lena Delta. - Savelieva, Larissa A; Dorozhkina, Marina V; Pavlova, Elena Yu (PANGAEA, 2002)
Studies of the annual pollen and spore deposition in different areas of the Lena Delta were undertaken for the first time in the Asian sector of the Arctic during the Russian-German ''LENA 98'' and ''LENA 99'' expeditions in the framework of the International ''Laptev Sea System-2000'' Project. To achieve this objective, three spore-pollen traps were set up along the meridional delta profile in accordance with the European Pollen Monitoring Programme for the period July 1998 to August 1999. A comparison between the results of spore-pollen analysis of the contents of traps and the surrounding vegetation was performed. The results confirmed the current spore-pollen spectra are comprised both of pollen and spores of the local plants and of long-distance pollen and spores. The dependence of the long-distance pollen deposition on the character of the wind regime of the region was established. The prevailing southerly and southeasterly wind direction determines the main pollen influx of tree species from the areas of their growth south of the delta. The features of the morphological structure and fossilization of pollen and the features of the productive capability and plant growing conditions are of large significance in the pollen transfer and deposition.
Pollen and spore deposition in different areas of the Lena Delta
Keywords: L-1; L-2; L-3; Laptev Sea System; Lena_1; Lena_2; Lena_3; Lena Delta, Siberia, Russia; Lena-Delta1998; LSS; Sampling on land; Trap, pollen; TRAPPOL